Descrição cariótica e novas ocorrências de cromossomos supranuméricos em Moenkhausia Eigenmann, 1903 (Characiformes: Characidae) - Nascimento, Cristiano Neves do [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The cytogenetic mapping of repetitive DNA has been applied in several studies in fish, which allowed a better characterization about the biodiversity and genomic evolution of Neotropical ichthyofauna. Among the several fish species living in this area, the genus Moenkhausia, one of the specious groups inside Characidae, is remarkable. From a cytogenetic point of view, this genus show variations in diploid numbers of 48 to 50 chromosomes, as well as the occurrence of B chromosomes in different species/populations. However, cytogenetic studies in Moenkhausia collected at different rivers from the Amazon and Upper Paraguay River basins are scarce, as well as studies investigating the chromosomal distribution of repetitive DNAs in different species. In this sense, the present study aimed to characterize the karyotypes of Moenkhausia cosmops, M. cf. forestii, M. cf. nigromarginata, M. oligolepis and Moenkhausia sp. collected at different sites in the Amazon and Upper Paraguay River basins. All species were analyzed using classical (conventional staining with Giemsa, localization of NORs by impregnation with Silver nitrate and C-banding) and molecular (fluorescent in situ hybridization with 5S and 18S rDNA, H1 histone, U2 snDNA and telomeric sequences (TTAGGG)n probes). All the herein analyzed species showed 2n=50 chromosomes, with different karyotype formulas. C-banding evidenced similar patterns of heterochromatin distribution in all species, except in M. cf. nigromarginata. Silver nitrate staining evidenced simple Ag-NORs in all species and FISH with 18S rDNA probes confirmed these results e revealed additional sites in M. oligolepis. The 5S rDNA was interstitially located in multiple sites in all species. Notably, both ribosomal sites were found in synteny in one population of M. oligolepis. The H1 histone sites were co-located in a single pair with 18S rDNA and the U2 snDNA was located at multiple sites in all species. Additionally, the ...

O mapeamento cromossômico de sítios de DNA repetitivo vem sendo realizado em vários estudos citogenéticos em peixes e tem permitido uma melhor caracterização da biodiversidade e evolução genômica da ictiofauna Neotropical. Dentre as diversas espécies de peixes distribuídas nesta importante área geográfica, podemos destacar o gênero Moenkhausia, um dos mais especiosos grupos de peixes da família Characidae. Do ponto de vista citogenético, este gênero demonstra variação do número diploide de 48 a 50 cromossomos, bem como a presença de microcromossomos B descritos para diferentes espécies/populações. No entanto, estudos citogenéticos de espécies de Moenkhausia coletadas em riachos de cabeceira da bacia Amazônica e bacia do Alto rio Paraguai ainda são incipientes, bem como os estudos relativos à distribuição de DNAs repetitivos nos genomas de diferentes espécies de Moenkhausia. Neste sentido, o presente trabalho teve como objetivo a caracterização cariotípica de Moenkhausia cosmops, M. cf. forestii, M. cf. nigromarginata, M. oligolepis e Moenkhausia sp. coletadas em diferentes rios e riachos de cabeceira da bacia Amazônica e bacia do Alto rio Paraguai. Todas as espécies foram analisadas através de técnicas citogenéticas clássicas (coloração com Giemsa, localização das RONs pela impregnação por Nitrato de Prata e bandamento C) e molecular (hibridação in situ fluorescente com sondas de DNAr 5S e 18S, histona H1, snDNA U2 e sequências teloméricas (TTAGGG)n). Todas as espécies/populações analisadas apresentaram 2n=50 cromossomos, porém com fórmulas cariotípicas distintas entre elas. O bandamento C revelou um padrão de bandas heterocromáticas similar entre essas espécies, exceto em M. cf. nigromarginata. A impregnação por Nitrato de Prata evidenciou Ag-RONs simples em todas as espécies analisadas. A FISH utilizando o DNAr 18S como sonda confirmou os resultados obtidos com o Nitrato de Prata e...
Keywords: Peixe - Genetica; Ictiofauna; Mapeamento cromossômico; DNA; Characideo; Fishes - Genetics